Dissociation from DNA of Type III Restriction–Modification enzymes during helicase-dependent motion and following endonuclease activity - Tóth, Júlia (Oxford University Press, 2012)
DNA cleavage by the Type III Restriction–Modification (RM) enzymes requires the binding of a pair of RM enzymes at two distant, inversely orientated recognition sequences followed by helicase-catalysed ATP hydrolysis and long-range communication. Here we addressed the dissociation from DNA of these enzymes at two stages: during long-range communication and following DNA cleavage. First, we demonstrated that a communicating species can be trapped in a DNA domain without a recognition site, with a non-specific DNA association lifetime of ∼200 s. If free DNA ends were present the lifetime became too short to measure, confirming that ends accelerate dissociation. Secondly, we observed that Type III RM enzymes can dissociate upon DNA cleavage and go on to cleave further DNA molecules (they can ‘turnover’, albeit inefficiently). The relationship between the observed cleavage rate and enzyme concentration indicated independent binding of each site and a requirement for simultaneous interaction of at least two enzymes per DNA to achieve cleavage. In light of various mechanisms for helicase-driven motion on DNA, we suggest these results are most consistent with a thermally driven random 1D search model (i.e. ‘DNA sliding’).